2017
DOI: 10.1021/acs.cgd.7b01336
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of Excipients on the Heterogeneous Crystallization and Dissolution Properties of an Active Pharmaceutical Ingredient

Abstract: This study is based on the heterogeneous nucleation of active pharmaceutical ingredients (APIs) 2 in the presence of various excipients widely used in the pharmaceutical industry. Carbamazepine (CBMZ) was successfully crystallized in the presence of the following heterosurfaces: α/β-4 Lactose, β-D-Mannitol, microcrystalline cellulose and carboxymethyl cellulose. The successful 5 crystallization of CBMZ FIII in the presence of all the excipients was confirmed by powder X-6 ray diffraction and scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 60 publications
(100 reference statements)
3
41
1
Order By: Relevance
“…These reductions in the induction time of CPB in the presence of excipients are significantly larger than those observed during the crystallisation of carbamazepine (CBMZ) or paracetamol (AAP) in the presence of MCC, previously reported. 18,41 In the case of CPB, as confirmed by PXRD ( Fig. 10), CPB-MeOH solvate crystallised in the presence of each of the three excipients; and as supported by single crystal data (Fig.…”
Section: Crystallisation Of Cpb In the Absence And Presence Of Excipimentioning
confidence: 65%
“…These reductions in the induction time of CPB in the presence of excipients are significantly larger than those observed during the crystallisation of carbamazepine (CBMZ) or paracetamol (AAP) in the presence of MCC, previously reported. 18,41 In the case of CPB, as confirmed by PXRD ( Fig. 10), CPB-MeOH solvate crystallised in the presence of each of the three excipients; and as supported by single crystal data (Fig.…”
Section: Crystallisation Of Cpb In the Absence And Presence Of Excipimentioning
confidence: 65%
“…Visual examination of number of vials/vessels crystallized (with time) using microscope or webcam is a common practice for determination of the nucleation kinetics (Arribas Bueno et al, ; Curcio et al, ; Diao et al, ; Hsu et al, ; Tan et al, ). Nucleation kinetics has also been determined by in‐line measurement of solution concentration using Fourier‐transform infrared spectroscopy (Verma et al, ) and turbidimetry (Chadwick et al, ; Quon et al, ). Moreover, simultaneous analysis of both physical form and concentration can be undertaken using near‐infrared spectroscopic probe as a process analyzer (Schaefer et al, ).…”
Section: Experimental Techniques For Heteronuclear Crystallizationmentioning
confidence: 99%
“…Verma et al demonstrated that carbamazepine crystallizes as a stable crystalline form III in the presence of microcrystalline cellulose and carboxymethyl cellulose, where the heteronucleants have improved the process efficiency with simultaneous improvement in dissolution performance of carbamazepine. The process was also scaled‐up to 600 ml from 20 ml with consistent particulate attributes of carbamazepine (Verma et al, ). Yazdanpanah et al demonstrated heterogeneous crystallization of PCM in presence of lactose monohydrate at scale of 5,000 ml.…”
Section: Experimental Techniques For Heteronuclear Crystallizationmentioning
confidence: 99%
See 2 more Smart Citations